Analisis Opini Publik Terhadap Pemilu 2024 Pada Media Sosial X - Tafana Destiana Larassetya; Arfian Suryasuciramdhan; Nuril Ulia Salsa; Ira Safaat Aeni (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The 2024 general election in Indonesia has become a global concern, with social media acting as the main platform for political interaction and political communication. This research aims to analyze public opinion regarding the 2024 elections in Indonesia expressed through Social Media X. Using content analysis and sentiment analysis methods, this research explores people's views, concerns and hopes regarding the upcoming elections. The research results show that there is significant polarization among Social Media X users in the election. These findings highlight the important role of social media in shaping public opinion and provide valuable insights for candidates and political parties in developing effective campaign strategies.